South African Renal Registry Annual Report 2015 - Davids, M Razeen; Marais, Nicola; Jacobs, Julian C (African Journal of Nephrology, 2017)
The fourth annual report of the South African Renal Registry summarises the 2015 data on renal replacement therapy (RRT) for patients with end-stage renal disease (ESRD) in South Africa. The South African population increased to 54.96 million in 2015, from 54.00 million in 2014. In December 2015, the number of patients with ESRD who were treated with chronic dialysis or transplantation stood at 10 360, a prevalence of 189 per million population (pmp). The prevalence was 167 pmp in 2013 and 178 pmp in 2014. The increasing prevalence observed is due mainly to the increased numbers of patients accessing haemodialysis in the private sector. In the public sector, which serves 84% of the South African population, the prevalence of RRT (71.9 pmp in 2015) remains at levels close to those reported in 1994 so that the disparity in access continues to increase. The disparities between provinces remain, with Limpopo and Mpumalanga the most under-served, as do the disparities between ethnic groups, with Blacks being the most under-served group.